Plants with known antagonistic properties against pests: how they influence non-target free-living soil fauna? - Kassimira Ilieva-Makulec; Michał Bielecki; Grzegorz Makulec (Studia Ecologiae et Bioethicae, 2017)
The aim of the study was to investigate the effect of three plant species with known antagonistic properties against pests on selected free-living species of soil fauna. The direct effects of aqueous extracts (from hemp leaves and garlic pulp) on the survival of representatives of nematodes, potworms and earthworms were studied. In the case of nematodes, the effects of hemp extracts on the egg production, total fertility and juvenile hatching efficiency were also assessed. Moreover the indirect plant impact (in the form of hemp litter added to the soil or through the root system during planting of castor bean) on soil nematodes was studied. The results of the bioassays confirmed the antagonistic effect of the plant extracts. The most sensitive to the hemp extract toxicity were nematodes, less potworms and at least earthworms. The toxicity of the hemp extract showed a clear dependence on its concentration. The garlic extract showed less toxicity to nematodes than the hemp extract did. The incubation of nematode females in the hemp extracts of different concentrations affected the rate of egg laying, the length of reproduction period and the hatching efficiency but did not affect their overall fertility. In soil, both the hemp litter and the castor plants had a positive indirect effect on the numbers of nematodes at least during the experiment.